The effect of cryotherapy on the reduction of pain levels in gout arthritis patients in Jambi city - Novrika, Bri; Akhriansyah, Mareta (International Journal Of Community Medicine And Public Health, 2020)
Background: Gouty arthritis is a disease caused by metabolic disorders with an increase in uric acid concentration which causes local joint pain. The management of gouty arthritis with pharmacological therapy usually uses several conventional drugs. The high prevalence of chronic pain experienced by sufferers has made the patient undergo non-pharmacological therapy with cold compresses (cryotherapy) to be more appropriate for joints with signs of inflammation such as redness and swelling that occur in patients with rheumatoid arthritis. Ice (ice packs) and ice water in the treatment of injuries and treatment modalities commonly used in the management of pain and injuries. Methods: This study used a quasi-experiment design with a two-group pre-test and post-test design approach. This study was conducted on patients with gout arthritis at PSTW Budi Luhur Jambi city with 16 respondent and control groups respectively. Data analysis in this study used univariate and bivariate using the independent t-test. Results: The results showed the average decreased levels of pain in patients with gouty arthritis in the control group without treatment pretest 3:50 whereas for the average posttest 3:19 and the average value decreased levels of pain in patients with gouty arthritis in the intervention group before performed cryotherapy 3:38 while for the average after treatment is 1.38, the statistical test p value is 0.000 Conclusions: The influence cryotherapy to decrease rate gout arthritis pain in patients PSTW Budi Luhur in the city of Jambi.